The role of lintels and parapets on the mechanical performance of multi-storey cross laminated timber shearwalls with openings. (15th March 2022) - Khajehpour, Mohammadreza; Casagrande, Daniele; Doudak, Ghasan
Highlights: Multi-storey CLT shearwalls with cut-off opening have been analyzed. CLT panel and mechanical anchors failure mechanisms are investigated. Effect of geometrical and mechanical properties on shearwall behavior is studied. Effect of lintel and parapet on the shearwall behavior is investigated. Mechanical behavior of monolithic and segmented shearwalls with opening is compared. Abstract: The current study presents the results of an extensive numerical analysis using a validated Finite Element model and aims at investigating the influence of the geometrical and mechanical properties of lintel beams and parapets on the stiffness and strength of multi-storey cross laminated timber (CLT) symmetric shearwalls with either door or window openings. The influence of construction techniques, where the opening is cut out of the panel or constructed using separate elements is investigated. The results of the analysis show that in general, monolithic models resulted in significantly higher strength and stiffness values compared to those obtained from models assuming segmented shearwalls. The assumptions associated with the connectivity between the various structural components in the wall may have a very significant effect on the internal forces and efficiency of the design. The study also particularly highlights the importance of the parapet on the overall behaviour and failure mechanism, even though no structural function is typically associated with it. The lintel height seemed to only play a significant role when no parapet is present, i.e. in the case of door openings, where height of the lintel was observed to directly influence the failure mechanism, with intermediate lintel heights leading to failure in the wood elements, while for relatively small or large values, the failure occurred in the mechanical anchors.